The Theology of Evangelization in Light of Pope Francis’ Catecheses on The Passion for Evangelization - Palus, Karol (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
This study examines the theology of evangelization in light of Pope Francis’ Wednesday catecheses titled The Passion for Evangelization. Through the use of analytical, synthetic, and comparative methods, the research identifies key aspects of evangelization, with particular emphasis on the sources of apostolic zeal. Foremost among these sources is the action of the Holy Trinity. Jesus Christ is presented as the paradigm of evangelization, while the Holy Spirit is emphasized as the principal agent of the evangelizing mission. Evangelization is also portrayed as an inherently ecclesial reality, in which the saints serve as exemplars for every evangelizer. A distinctive feature of Pope Francis’ approach to evangelization is his strong emphasis on pastoral conversion and the active involvement of the laity. His catecheses represent a development of the teachings of the Second Vatican Council and the post-conciliar pontiffs, especially Pope Paul VI.